Intersections between Jews and Media - Katz, Maya Balakirsky (Brill research perspectives in religion and the arts, 2019)
In this volume, the relationship between Jews and media is not only vividly illustrated, but it is consciously drawn into the formation of modern Jewish history and modern media. Maya Balakirsky Katz addresses key Jewish-media intersections in which Jews and mass media implicated (or were implicated by) one another. In this study, Katz discusses the relationship that Jews have had with mass media forms of print, film, photography, advertising, and postcards within the periods that these media have gained cultural ascendancy. These historical moments are tethered to a broader conversation addressing the major theoretical issues at the center of the discourse on Jews and media. Bearing this mutually constructive relationship in mind, Intersections between Jews and Media offers both a tangible demographic portrait of the real Jews who entered mass media and lays a theoretical and methodological framework for more qualitative analyses.